Autocrine CCL5 promotes tumor progression in esophageal squamous cell carcinoma in vitro. (October 2018) - Wu, Yi-Cheng; Shen, Yung-Chi; Chang, John Wen-Cheng; Hsieh, Jia-Juan; Chu, Yen; Wang, Cheng-Hsu
Highlights: ESCC cells derived from metastatic lymph nodes produce higher levels of CCL5 than those from primary lesions. Autocrine CCL5 loop promotes ESCC progression in vitro . Maraviroc blocks ESCC migration and invasion in vitro, implying its therapeutic potential in this cancer entity. Abstract: The pro-tumoral effects of CCL5 have been identified in numerous cancer types. We successfully cultivated 4 esophageal squamous cell carcinoma (ESCC) cell lines, including TWES-1, TWES-3 and a pair of cell lines derived from primary lesion (TWES-4PT) and metastatic lymph node (TWES-4LN) of the same patient. Whole genome screening showed that TWES-4LN expressed higher levels of CCL5 compared to that of TWES-4PT; quantification of protein secretion displayed comparable results, suggesting that CCL5 could be associated with lymph node metastasis in ESCC. CCL5 knockdown by siRNA significantly reduced basal growth rate, tumor migration and invasiveness in the paired cell lines; whereas this treatment induced cell apoptosis in TWES-1 and TWES-3. CCR5 antagonist maraviroc significantly inhibited tumor migration and invasion in the paired cell lines without affecting tumor growth. Collectively, these results suggest that CCL5 autocrine loop may promote ESCC progression; targeting the CCL5/CCR5 axis could be a potential therapeutic strategy for this deadly disease.